2019
DOI: 10.2147/idr.s227823
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Ambient Air Pollution and Elevated Risk of Tuberculosis Development</p>

Abstract: BackgroundBroad-scale evidence has shown the significant association between ambient air pollutants and the development of tuberculosis (TB). However, the impact of air quality on the risk of TB in Taiwan is still poorly understood.ObjectiveTo develop a probabilistic integrated population-level risk assessment approach for evaluating the contribution of ambient air pollution exposure to the risk of TB development among different regions of Taiwan.Materials and methodsA Bayesian-based probabilistic risk assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
(66 reference statements)
2
26
0
Order By: Relevance
“…Our study showed a positive correlation between NO2 and TB, two time series studies in Chengdu and Hefei also reached similar conclusions (Zhu and Xia et al, 2018;Huang and Ding et al, 2020). A study in Taiwan has shown that NO2 is associated with tuberculosis which contributed 1.2-9.8% to developing TB (Lin and Lin et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed a positive correlation between NO2 and TB, two time series studies in Chengdu and Hefei also reached similar conclusions (Zhu and Xia et al, 2018;Huang and Ding et al, 2020). A study in Taiwan has shown that NO2 is associated with tuberculosis which contributed 1.2-9.8% to developing TB (Lin and Lin et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…If the host organism has a reduced ability to clear and limit infection with Mycobacterium tuberculosis , it is highly susceptible to infection with the bacteria. It has been suggested that lifestyles, work environment, and outdoor air quality may have a certain impact on the health of the host [ 3 , 4 ], especially smoking and passive smoking in a closed environment can not only reduce the resistance of the respiratory organs, making it easy for harmful microorganisms such as Mycobacterium tuberculosis to invade the lungs and make tuberculosis more likely to occur, causing bacteria or viruses infection while the resistance of the respiratory organs is further reduced, making TB more difficult to cure [ 5 , 6 ]. Studies have found that differences in human genetic polymorphisms may lead to differential susceptibility to TB [ 7 ], and susceptible individuals must pay more attention to lung protection and screening.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions such as clean cook stoves to reduce the adverse effects of indoor air pollution merit rigorous evaluation [50], particularly in high TB burden countries in Asia and the Pacific, where the prevalence of both indoor air pollution and TB is high. Clean energy is also expected to reduce outdoor air pollution and improve ambient air quality, which can reduce the risk of TB [55].…”
Section: Sdg Goal 7: Affordable and Clean Energymentioning
confidence: 99%